2018
DOI: 10.1080/23746149.2017.1417055
|View full text |Cite
|
Sign up to set email alerts
|

Metafluidic metamaterial: a review

Abstract: Metafluidic metamaterial is a metamaterial the optical response of which is dependent on fluid contributed metamolecules. The dependence originates either from a fluid background coupling to the metamolecule or from the resonance in a liquid structured metamolecule. Different liquid materials including water, liquid crystal, and liquid metals are applied to realize the metafluidic metamaterial. Sophisticated technologies like electric bias and microfluidic system have been used for active control of metafluidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 150 publications
0
27
0
Order By: Relevance
“…More intriguingly, the mechanical resonance of piezoelectric actuators is sensitive to temperature variations; therefore, they can be integrated with metamaterial absorbers to form EM wave detectors 75 . In addition to solid-state actuators and sensors, microfluidic devices can also be used to construct tunable metamaterials 76,77 . In this type of device, microfluidic channels, which are patterned as arrays, can carry liquid metals (such as mercury) instead of water-based solutions to form metamaterials.…”
Section: Metamaterials and Mems/nemsmentioning
confidence: 99%
“…More intriguingly, the mechanical resonance of piezoelectric actuators is sensitive to temperature variations; therefore, they can be integrated with metamaterial absorbers to form EM wave detectors 75 . In addition to solid-state actuators and sensors, microfluidic devices can also be used to construct tunable metamaterials 76,77 . In this type of device, microfluidic channels, which are patterned as arrays, can carry liquid metals (such as mercury) instead of water-based solutions to form metamaterials.…”
Section: Metamaterials and Mems/nemsmentioning
confidence: 99%
“…This leads to a new tool for the optimization of the resonant responses of the system and thus provides tunability. This aim is possible by using MEMS/ NEMS-in which the electrical and mechanical elements are integrated-and also microfluidic channels and stretchable materials in the system [75][76][77][78][79][80][81][82][83][189][190][191][192][193][194][195]. MEMS/NEMS are composed of micro-or nanometer scale components and have the ability to function in the micro-and nano-scale.…”
Section: Active Mpas Based On Mems Microfluidic Channels and Elastimentioning
confidence: 99%
“…There are several different categories of active materials that are available in nature and that can be employed to design active metamaterials. These materials can be categorized as transparent conductive oxides (TCOs) [67,[86][87][88][89][90], superconductors [91,[92][93][94][95][96], ferroelectrics [such as strontium titanate (STO) and BaSrTiO 3 (BST)] [69,85], ferrites and magnetically tunable materials [97][98][99][100][101], liquid crystals (LCs) [102][103][104][105][106], molecules and polymers [107,108], liquid iron [109,110], semiconductors [71], graphene [111][112][113][114][115][116], and phase-change materials (PCMs) [117][118][119][120][121]. The previous reviews about metamaterial light absorbers have mainly focused on the investigation of theoretical backgrounds, different designs, and applications of passive structures [122][123][124][125]…”
Section: Introductionmentioning
confidence: 99%
“…Liquid dielectric antennas have drawn a significant amount of attention for a number of reasons, (1) conformability: any antenna shape can be achieved due to the nature of liquid; (2) reconfigurability (both physical and chemical): it is easy to change the resonance frequency and bandwidth by changing the height/width of the liquid stream and the chemical composition; (3) low cost: liquid dielectrics are cheap and easily available compared to more costly liquid metals (e.g., mercury (Hg) or eutectic gallium indium allow (EGaIn)), (4) transparent and biocompatible, (5) high permittivity which helps to miniaturize antennas. Besides antennas, liquid dielectric materials have been applied in the field of metamaterials and metasurfaces [14][15][16][17], for the design of reconfigurable frequency selective surfaces (FSS) [18], absorbers [19][20][21][22][23], sensors [24], reflect-arrays and array lenses [25], and polarization converters [18]. However, these topics fall beyond the scope of the present review and the details can be found in the review papers [15,26].…”
Section: Introductionmentioning
confidence: 99%
“…Besides antennas, liquid dielectric materials have been applied in the field of metamaterials and metasurfaces [14][15][16][17], for the design of reconfigurable frequency selective surfaces (FSS) [18], absorbers [19][20][21][22][23], sensors [24], reflect-arrays and array lenses [25], and polarization converters [18]. However, these topics fall beyond the scope of the present review and the details can be found in the review papers [15,26].…”
Section: Introductionmentioning
confidence: 99%